Male and Female EFL Teachers’ Mood Structure in Classroom Interaction - Erlinda Kurniatillah, Ratu; Husna, Nida; Alek, Alek; Hidayat, Didin Nuruddin; Hamid, Farida (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research study aimed to examine the talks of male and female EFL teachers. This study aims to determine how male and female EFL teachers realise mood differently and how they recognize it in their discussions and roles as teachers. The plan was to use a descriptive-qualitative research design. Observation, audio recording, and field notes were used to collect data. Mood structure analysis was used to analyze data. To provide a more detailed analysis, utterances are classified based on their description, meaning, and code. This study's findings are: (1) A male teacher found 26 statement mood utterances, 26 interrogative mood utterances, 20 declarative mood utterance variations, and 2 offer mood utterances. Meanwhile, female teachers identified 23 statement moods, 17 interrogative moods, 5 commands, and 1 offer moods (2) for using mood structures in male and female teacher discourse; statement and interrogative moods are the most often employed moods during the teaching and learning process. (3) the most widely utilized kind of mood structure is declarative. It happens because teaching is a teacher's primary responsibility.